Digital Marketing Training in the Development Efforts of Aliena Jaya Furniture MSMEs in Klokah Village - Ali, Ali; Taufiqurrohman, Muhammad; Nurhidayah, Wanda; Hidayah, Aini (Jurnal Pengabdian kepada Masyarakat Khaira Ummah, 2023)
KKN UNISNU Batch XV Klokah Group conducted digital marketing training and assistance to Mr. Abdul's MSMEs Furniture business located in Klokah Village, Kunduran sub-district, Blora district, Central Java province. The purpose of this community service is to develop Pak Abdul's furniture business by providing insight into marketing strategies that started in the traditional way and then changed to keep up with existing technological developments. In solving the problem of MSMEs furniture belonging to Mr. Abdul using the method of socialization, training, application of technology, assistance and sustainability. In the socialization and training stages the KKN Team provided material presentation on the importance of the role of digital marketing for the development of a business, provided tutorials for creating accounts on digital media such as Shopee and Instagram to market their products. With this community service, it is hoped that it can provide benefits for MSME actors in Klokah village, namely by adding information to develop their business by marketing and selling products through ecommerce and social media as a medium or tool for marketing products.